2015
DOI: 10.1007/s11199-015-0486-9
|View full text |Cite
|
Sign up to set email alerts
|

Gender Gaps in Overestimation of Math Performance

Abstract: In the United States, men are more likely to pursue math-intense STEM courses and careers than women. This investigation explored whether positivity bias in the degree to which people overestimate their past performance contributes to this gender gap. To find out, two studies were conducted with undergraduate college students in the Southern United States. In Study 1, participants (n=122) completed a math test and estimated the percent they had solved. They then were given feedback and completed a second math … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 55 publications
6
47
0
2
Order By: Relevance
“…Another well-documented stereotype women in STEM face is the cultural stereotype regarding women and weak mathematics ability (Bench et al 2015;Luong and Knobloch-Westerwick 2017;Rea 2015;Shaffer, Marx, and Prislin 2013;Shapiro and Williams 2012;Thoman et al 2008). Park et al (2016) even found women (but not men) were more likely to show worse mathematics performance and less interest in STEM careers to seem desirable when pursuing smarter romantic partners on campus.…”
Section: Stereotypesmentioning
confidence: 99%
“…Another well-documented stereotype women in STEM face is the cultural stereotype regarding women and weak mathematics ability (Bench et al 2015;Luong and Knobloch-Westerwick 2017;Rea 2015;Shaffer, Marx, and Prislin 2013;Shapiro and Williams 2012;Thoman et al 2008). Park et al (2016) even found women (but not men) were more likely to show worse mathematics performance and less interest in STEM careers to seem desirable when pursuing smarter romantic partners on campus.…”
Section: Stereotypesmentioning
confidence: 99%
“…The literature on males' endorsement of gender/ STEM stereotypes is comparatively limited, but offers evidence that men are generally more likely to endorse such stereotypes than women, and that, in particular, men in STEM fields are very likely to hold gender stereotypical views (Nosek et al, 2002;Smeding, 2012;Young et al, 2013). Again, these patterns make sense, particularly as men who are pursuing STEM benefit from the stereotype that they are naturally gifted and prone to be successful in their chosen field; indeed, this belief can help buffer negative psychological effects of any instance of low performance, as poor performance can be attributed to bad luck or extenuating circumstances, and not their actual ability (Bench, Lench, Liew, Miner, & Flores, 2015;Niederle & Vesterlund, 2010). Yet given that males are arguably the most likely source of females' exposure to stereotypes, it is critical to expand upon the limited research in this area to better understand males' beliefs.…”
Section: Who Believes the Hype?mentioning
confidence: 99%
“…Again, these patterns make sense, particularly as men who are pursuing STEM benefit from the stereotype that they are naturally gifted and prone to be successful in their chosen field; indeed this belief can help buffer negative psychological effects of any instance of low performance, as poor performance can be attributed to bad luck or extenuating circumstances, and not their actual ability (Bench et al, 2015; Niederle & Vesterlund, 2010). Yet given that males are arguably the most likely source of females’ exposure to stereotypes, it is critical to expand upon the limited research in this area to better understand males’ beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been well documented that, even when men and women had similar science performance, men tended to be overconfident about their science competence. which led to a stronger belief in their science identity, compared with women who tended to underestimate their science competence (Bench, Lench, Miner, Flores, & Liew, ; Watt, ). For another example, science identity was found to be strongly related to motivations such as communal goals or agency goals (e.g., Diekman, Weisgram, & Belanger, ).…”
Section: Introductionmentioning
confidence: 99%